Public housing myths : perception, reality, and social policy - Bloom, Nicholas Dagen, 1969-; Umbach, Gregory Holcomb; Vale, Lawrence J., 1959-; Heathcott, Joseph, 1968- (Cornell University, 2015)
Popular opinion holds that public housing is a failure; so what more needs to be said about seventy-five years of dashed hopes and destructive policies? Over the past decade, however, historians and social scientists have quietly exploded the common wisdom about public housing. Public Housing Myths pulls together these fresh perspectives and unexpected findings into a single volume to provide an updated, panoramic view of public housing. With eleven chapters by prominent scholars, the collection not only covers a groundbreaking range of public housing issues transnationally but also does so in a revisionist and provocative manner. With students in mind, Public Housing Myths is organized thematically around popular preconceptions and myths about the policies surrounding big city public housing, the places themselves, and the people who call them home. The authors challenge narratives of inevitable decline, architectural determinism, and rampant criminality that have shaped earlier accounts and still dominate public perception. Contributors: Nicholas Dagen Bloom, New York Institute of Technology; Yonah Freemark, Chicago Metropolitan Planning Council; Alexander Gerould, San Francisco State University; Joseph Heathcott, The New School; D. Bradford Hunt, Roosevelt University; Nancy Kwak, University of California, San Diego; Lisa Levenstein, University of North Carolina at Greensboro; Fritz Umbach, John Jay College of Criminal Justice, CUNY; Florian Urban, Glasgow School of Art; Lawrence J. Vale, Massachusetts Institute of Technology; Rhonda Y. Williams, Case Western Reserve University.